2010
DOI: 10.4995/wrs.2010.777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of housing system (wire cage versus group-housing) and in-house air quality parameters on the behaviour of fattening rabbits

Abstract: ABSTRACT:In the same room of an experimental rabbit house 2 housing systems were compared, namely three pens to keep rabbits on bedding and six wire cages for unbedded rabbit keeping. In total, 69 New Zealand White crossbred rabbits 8-12 wk old were used in the study. The rabbits were kept in groups with 0.6 m 2 fl oor area per animal in pens with thinly scattered straw. Wire cages had no bedding and there were 4 rabbits in each cage and 0.4 m 2 fl oor area per rabbit. The study lasted for 8 wk. Rabbit behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
1
10
1
Order By: Relevance
“…Sancilio et al (1999) reported inhalable PM concentrations to be in the range between 0.75 to 3.62 mg/m 3 , and from 0.24 to 0.90 mg/m 3 for the respirable fraction. Nevertheless, Ribikauskas et al (2010) reported higher concentrations for inhalable PM for rabbits kept in groups in straw pens than those reported for size-fractioned PM for rabbits kept in cages in our study. Although direct comparison between occupational health size fractions and PM10 and PM2.5 is not straightforward because it depends on sampling instrument cut-off curves and the sampling conventions followed, our results for PM concentrations are found within the lower ranges of the values reported in the literature for occupational health size fractions.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Sancilio et al (1999) reported inhalable PM concentrations to be in the range between 0.75 to 3.62 mg/m 3 , and from 0.24 to 0.90 mg/m 3 for the respirable fraction. Nevertheless, Ribikauskas et al (2010) reported higher concentrations for inhalable PM for rabbits kept in groups in straw pens than those reported for size-fractioned PM for rabbits kept in cages in our study. Although direct comparison between occupational health size fractions and PM10 and PM2.5 is not straightforward because it depends on sampling instrument cut-off curves and the sampling conventions followed, our results for PM concentrations are found within the lower ranges of the values reported in the literature for occupational health size fractions.…”
Section: Discussioncontrasting
confidence: 51%
“…2012, 20: 1 -11 doi:10.4995/wrs.2012.1035© WRSA, UPV, 2003, threatening the environment (plants and organisms), causing vegetation stress and ecosystem alteration (Grantz et al, 2003). Although PM concentrations and emissions have been characterised in poultry and pig production systems (Costa and Guarino, 2009;Lacey et al, 2003), little is known about PM concentration and emissions in and from rabbit houses (Navarotto et al, 1995;Ribikauskas et al, 2010). Although PM concentrations in rabbit farms seem to be low compared to other livestock species (Cambra-López et al, 2008), the emission of PM into the atmosphere could be relevant due to the high ventilation rates observed in those European regions where rabbits are reared (typically Mediterranean countries) (Calvet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with other authors World Rabbit sci. 21: 107-110 working with conventional cages and similar conditions such as Princz et al (2008a) and Ribikauskas et al (2010), who found a similar time budget (between 66.9 and 66.2% respectively).…”
Section: Resultsmentioning
confidence: 92%
“…It must be considered that this category includes self-body care and exploratory behaviours. Self-body care is known to be a time-consuming behaviour (8.48% of time according to Ribikauskas et al, 2010), contributing to increase the frequency of "others". In addition, exploratory behaviours in the present study can be expected to be higher than previously reported values (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The mean frequency and duration (min.) spent in the following behavioral patterns were scored according to Ribikauskas et al (2010).…”
Section: Behavioural Observations and Productive Performancementioning
confidence: 99%